Microcystin-LR exposure interfered maintenance of colonic microenvironmental homeostasis in rat. (March 2023) - Liu, Yang; Qi, Chun-Li; Li, Da-Wei; Li, Hong-Ye; Li, Rui-Man; Yang, Wei-Dong
Abstract: Microcystin-leucine arginine (MCLR) is a phycotoxin produced by cyanobacteria. As a hepatotoxin, increasing evidence suggests that it has some negative effects on the mammal gastrointestinal tract, but further studies are warranted. In this study, we investigated the effects of MCLR on the intestinal epithelial microenvironment by oral administration of MCLR. As expected, MCLR at doses of 200 and 400 μg kg −1 bw showed hepatorenal toxicity in rats but without significant gastrointestinal symptoms. MCLR exposure decreased the thickness of the colonic epithelial mucus layer, and down-regulated the expression of main mucin protein (MUC2), cytoskeletal assembly-related genes ( Arpc1a, Enah ) and cytoskeletal stability-related genes ( Ptk2, Prkca, Actn1, Pxn, Tln1, Cttn, Vcl ) in colonic tissue to varying degrees, but did not affect the expression of cell connection-related genes including Zo1, Ocln, Cldn2 and Cdh1 . In addition, MCLR exposure had a limited effect on gut bacterial diversity but clearly enriched specific bacteria. Prevotella, which plays a crucial role in balancing health and disease, was inhibited, whereas Muribaculaceae concerning the epithelial barrier, was promoted. Together, our findings demonstrate that MCLR exposure can weaken the colonic epithelial barrier by interfering with the stability of the cytoskeleton, which in turn exacerbates the homeostasis maintenance in the intestinal microenvironment.